The Application of The Analytic Hierarchy Process (AHP) In Job Evaluation Model in Municipal Enterprise in Poland - Janusz CZEKAJ; Marek JABŁOŃSKI; Anna PRUSAK (Communications of International Proceedings, 2022)
The objective of this paper is to demonstrate the possibility of application the analytic hierarchy process in job evaluation model. Two hierarchical models of job evaluation have been constructed: for manual (“blue-collar”) workers and for intellectual (“white-collar”) employees. Each of them consisted of four main criteria, namely: Work complexity, Responsibility, Body workload, and Work demands. The analysis of these models was based on pairwise comparisons, judgments expressed by the experts responsible for human resource management in one of the largest municipal enterprises located in Southern Poland. Thirty-three respondents participated in the study. The results were analyzed for each of them individually, and then the priorities were aggregated (aggregation of individual priorities, AIP). The results showed the significant importance of factor called Responsibility for people (safety), for evaluation of both manual workers and intellectual employees.
Keywords: AHP; job evaluation; white-collars; blue-collars; work complexity; responsibility; workload.